Analysis Of Water Distribution Networks In A Supply System Drinking Water In STL Ulu Terawas Districts Musi Rawas District - okma yendri okma yendri (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
AbstractClean water is a vital need of living things, especially for human beings who live spread throughout the earth's surface both in urban and rural areas. This study aims to determine the discharge and the condition of the existing water sources used by SPAM, STL Ulu Terawas Sub-district, to find out the elevation of each pipe junction of the STL Ulu Terawas SPAM pipe. Provide the most efficient alternative network in meeting the needs of the community. The method of analyzing the water distribution network in the drinking water supply system in STL Ulu Terawas District, Kabupaten Musi Rawas using EPANET 2.0 software. The EPANET simulation results show that the water discharge value at the SPAM STL Ulu Terawas Musi Rawas Regency is getting lower as the water pressure decreases at junction 4 (four) the water discharge is 30 liters/second until junction 13 (thirteen) the water discharge is 15 liters/second. The EPANET simulation results show that the elevation conditions at the SPAM STL Ulu Terawas Musi Rawas Regency are too high from the water source, such as at junction 2 (two) the elevation is 51 meters, while the elevation at junction 10 (ten) elevation is 62 meters. That's what causes the water discharge to get further and lower its speed. The EPANET simulation results show that the water distribution network of SPAM STL Ulu Terawas has failed, such as at junction 4 (four) the water discharge is 30 liters/second while junction 13 (thirteen) water discharge is 15 liters/second, which means it can be explained that the water distribution network At SPAM STL Ulu Terawas Kabupatn Musi Rawas, the water has not been able to drain properly.